Culturally sensitive and community-based HIV/AIDS prevention messages for African American women - Nightingale, Sarah (Kansas State University, 2008)
African American women account for almost two thirds of all women living with HIV/AIDS in the United States. These epidemiological data highlight a critical need to develop intervention campaigns that communicate risk reduction strategies to this population. Using the framework of the Information-Motivation-Behavioral skills (IMB) model, the current study recruited African American women to view one of four brochures in which two experimental treatments were crossed: African American/individual prevention; Caucasian/individual prevention; African American/community prevention and Caucasian/community prevention. Attitude toward the message, risk perception, self-efficacy and community responsibility were measured through a survey questionnaire. Results showed that participants who viewed brochures featuring African American women displayed more favorable attitudes, increased self-efficacy, increased community responsibility and increased perceived risk for other African American women. The limitations of this study and implications for future research and development of HIV/AIDS prevention strategies are discussed.
Keywords: HIV/AIDS; communication; culture; Information-Motivation-Behavioral skills; Health Sciences, Education (0350); Mass Communications (0708)